PERANAN KEPALA DISTRIK DALAM PERENCANAAN PEMBANGUNAN KAMPUNG (Suatu Studi Di Distrik Buruway Kabupaten Kaimana Provinsi Papua Barat) - Oruw, Maikel J; Kiyai, Burhanuddin; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACTThis study aims to determine the role of the district development planning in the District Kampung BuruwayKaimana district, West Papua Province. By applying the method of descriptive and qualitative approach, teninformants selected as a data source (sources) to be interviewed, then analyzed using interactive techniques.The analysis showed that the District Chief Buruway quite instrumental in facilitating the preparation of theMedium Term Development Plan of the village, the village Government Work Plan and Budget Plan for the village;as well as facilitating the decision-making role in the village and the decision of the Head of the village. DistrictChief Buruway also always willing to facilitate the implementation of the tasks and functions of KampungConsultative Body (Bamuskam) and social institutions / other traditional institutions.It was concluded that the District Chief Buruway also instrumental in carrying out oversight throughmonitoring and evaluation of the process of preparing village development plans to fit with the vision, mission, goalsand objectives of the regional administration and the provisions of existing law. It is recommended that DistrictChief perlua enhance its role in safeguarding the implementation of programs of village development in order notto deviate from the plan that has been dipustuskan in Musrembangkam; and include hometown competentauthorities, especially officials Bamuskam for training village development plans, especially the preparation ofRAPBKam.Keywords : Role of the Chief District, Village Development Planning.